Furiously happy [compact disc, unabridged] : {a funny book about horrible things} - Lawson, Jenny, 1973- (Macmillan Audio, 2015)
"In Furiously Happy, #1 New York Times bestselling author Jenny Lawson explores her lifelong battle with mental illness. A hysterical, ridiculous book about crippling depression and anxiety? That sounds like a terrible idea. But terrible ideas are what Jenny does best. As Jenny says: "Some people might think that being 'furiously happy' is just an excuse to be stupid and irresponsible and invite a herd of kangaroos over to your house without telling your husband first because you suspect he would say no since he's never particularly liked kangaroos. And that would be ridiculous because no one would invite a herd of kangaroos into their house. Two is the limit. I speak from personal experience. My husband says that none is the new limit. I say he should have been clearer about that before I rented all those kangaroos. "Most of my favorite people are dangerously fucked-up but you'd never guess because we've learned to bare it so honestly that it becomes the new normal. Like John Hughes wrote in The Breakfast Club, 'We're all pretty bizarre. Some of us are just better at hiding it.' Except go back and cross out the word 'hiding.'"Furiously Happy is about "taking those moments when things are fine and making them amazing, because those moments are what make us who we are, and they're the same moments we take into battle with us when our brains declare war on our very existence. It's the difference between "surviving life" and "living life". It's the difference between "taking a shower" and "teaching your monkey butler how to shampoo your hair." It's the difference between being "sane" and being "furiously happy."Lawson is beloved around the world for her inimitable humor and honesty, and in Furiously Happy, she is at her snort-inducing funniest. This is a book about embracing everything that makes us who we are - the beautiful and the flawed - and then using it to find joy in fantastic and outrageous ways. Because as Jenny's mom says, "Maybe 'crazy' isn't so bad after all." Sometimes crazy is just right"--